2019
DOI: 10.1177/0193945919866475
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters and Health-related Quality of Life in Chinese patients with Chronic Obstructive Pulmonary Disease

Abstract: This study aimed to identify symptom clusters of chronic obstructive pulmonary disease (COPD) and to examine the relationship between symptom clusters and health-related quality of life (HRQoL). It included 154 hospitalized patients with COPD. The majority of the participants (88.6%) were aged 60 years and above, and the numbers of men and women were approximately equal (men: 55.2%). The Charlson Comorbidity Index (CCI), the Memorial Symptom Assessment Scale (MSAS), and the Chinese version of the Clinical COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 50 publications
5
29
1
Order By: Relevance
“…Our study identi ed that all the symptom clusters were signi cantly correlated with HRQoL in COPD population. The result of a correlation between the depression-anxiety symptom cluster and HRQoL in this study is consistent with a previous study, which revealed that psychological symptom clusters are a signi cant predictor of HRQoL [17]. Our results reinforce the signi cant effect of psychological symptom clusters on HRQoL in people living with COPD.…”
Section: Association Between Symptom Clusters and Health-related Qualsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study identi ed that all the symptom clusters were signi cantly correlated with HRQoL in COPD population. The result of a correlation between the depression-anxiety symptom cluster and HRQoL in this study is consistent with a previous study, which revealed that psychological symptom clusters are a signi cant predictor of HRQoL [17]. Our results reinforce the signi cant effect of psychological symptom clusters on HRQoL in people living with COPD.…”
Section: Association Between Symptom Clusters and Health-related Qualsupporting
confidence: 92%
“…Validation of the concept of symptom cluster is complicated and di cult because evaluating symptom interrelationships manifests a host of methodological challenges, speci cally the study design, theoretical framework, measurement tools, symptom dimensions, statistical methods to identify the cluster, statistical "cut-off" points to de ne clusters, characteristics of study samples may all contribute to these inconsistencies of symptom clusters [12]. Among previous studies, different symptom assessment tools were used, and each involved a different array of symptoms [13][14][15][16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between HRQoL and age was discussed in several studies, and the results were controversial. Almost seven studies were reported a positive correlation between age and HRQoL [11] [23]- [28]. On the other hand, an old study carried out by Wijnhoven and his colleagues [48] reported a controversial result indicating better HRQoL in current smokers.…”
Section: Predictors Related To Sociodemographic and Clinical Variablesmentioning
confidence: 99%
“…Only four studies (Park & Larson, 2014;Park et al, 2013;Srirat et al, 2014Srirat et al, , 2015 reported an estimated sample size using appropriate statistical methods. Eight studies (Lim et al, 2017;Park & Larson, 2014;Park et al, 2012Park et al, , 2013Srirat et al, 2014Srirat et al, , 2015Wu et al, 2020;Yang et al, 2020) clearly defined the target/reference population and had an appropriate sampling frame. Two studies (Breland et al, 2015;Li et al, 2013) had no selection process.…”
Section: Quality Of Studiesmentioning
confidence: 99%